Citation analysis based on Google Scholar - Oh, Kalyn Hui Yi (2014)
Google Scholar is an increasingly popular search engine with the largest bibliographic database for citation analysis that is accessible to anyone unlike other bibliographic databases which may incur monthly fees. With the increase of publications of scholarly papers, there is an increase in demand for quality measurement of papers for assessing the author’s publication works. The evaluations of author’s publications rely on citation analysis as to achieve an unbiased evaluation of an author’s work. H-index is one of the mostly used citation metric, thus, two unique additional calculations of h-index with unknown authors’ citations per paper and citations without self-citation of the author were included and compared against the original h-index calculation in this report. Hence, this report presents the study of the citation analysis of citation records based on Google Scholar.